Cerebral structure and intraventricular haemorrhage in the neonate: a real-time ultrasound study. Issue 6 (June 1981) - Levene, M I; Wigglesworth, J S; Dubowitz, V
Abstract : A method for systematic scanning of the neonatal brain with real-time ultrasound is described, and the linear array is compared with mechanical sector scanners. Anatomical landmarks recognised on axial, coronal, and parasagittal scans are verified by comparison with brain slices at necropsy. A prospective study of 50 infants admitted consecutively to the neonatal unit at this hospital showed intraventricular haemorrhage in 18 (36%). These 18 infants included 10 (43%) out of 23 of birthweight less than or equal to 1500 g, and 3 (27%) out of 11 of birthweight 1501-2000 g. An unexpected feature was the recognition of intraventricular haemorrhage in 5 of the 13 infants greater than 2000 g birthweight. On sequential daily scans intraventricular haemorrhage was diagnosed most often in the first 2 days of life and abnormal ventricular echoes persisted for up to 12 days thereafter. Late development of hydrocephalus was recorded in 2 infants. Real-time ultrasound provides the neonatologist with a practical method for diagnosis and monitoring of intracranial lesions in the ill neonate and is a valuable, non-invasive, and safe tool for studying the pathophysiology of neurological handicap in infancy.